Scat omnibook for vocalists and C instruments - Johnson, Mark 1957- (Hal Leonard Corporation, 2015)
Instrumentalists, get ready for some fun. For the first time ever, you can play the exact lines as scatted by some of the greatest jazz legends of all time. Of course singers can get in on the fun, too. However no lyrics are included for the scat solos, as the spelling of syllables is too varied and numerous
Unaccompanied melodies, principally for 1 voice; with lyrics, chord symbols, metronome markings, and without scat syllables
"Transcribed exactly from the original recordings."
"The history of scat"--Page 3
Includes index
Keywords: Jazz vocals / Lead sheets; Jazz / Lead sheets; Scat singing; Jazz; Lead sheets; Songs